Fundamental Requirements for Smartphone Commercial Applications Development for Arabic Societies: Evidence from Three Gulf Cooperation Council States - Bahaddad, Adel A. (International Journal of Computing Sciences Research, 2017)
Purpose   – This study focuses on the requirements of commercial applications in the Arabic region, specifically in three Gulf Cooperation Council (GCC) states, which are Saudi Arabia (KSA), Qatar and the United Arab Emirates (UAE).  Method – It used quantitative survey to collect the opinion of the target audience in KSA, Qatar, and UAE. Results – Identifying commercial application requirements in this study is necessary for two main reasons: first, current studies that present requirements are lacking; second, studies in this field vary from one region to another and from one community to another. Thus, identifying the requirements according to specific communities in this study will enable the broad use of the applications. Contributions – The results provide 20 fundamental functions that should be included in m-commerce applications to be acceptable in Arabic society, as they may contribute to developing the mechanism of creating and designing smartphone commercial applications in developing companies. These functions are divided into three main parts; namely, technical, organisational and social functions. Research Implications – These functions are influenced by various stakeholders such as consumers, sellers, and application designers. These three parties are the main decision makers about how to design the m-commerce application functions.